Acute effects of a resistance tubing training device on baseball swing kinematic - Barfield, J. W.; Oliver, G. D (Journal of Athletic Enhancement, 2018)
Objective: The purpose of this study was to assess the acute kinematic changes that occur on the youth baseball swing following use of a resistance tubing training device.